World's greatest entertainer - Anonymous (Uttar Pradesh : Wonder House, 2023)
A well-researched book which celebrate the achievements of talented film-makers and actors who have contributed to the development of cinema with their talent, hard work and success stories. Age appropriate content, fun facts and bold illustrations will appeal to the curiosity of young inquisitive minds and help them develop their reading skill and general knowledge.
Keywords: Biographies -- Juvenile Literature; Inspirational Personalities -- Juvenile Literature